PELATIHAN PRODUKSI GANTUNGAN KUNCI RESIN BAGI PEREMPUAN SEBAGAI UPAYA PEMBERDAYAAN EKONOMI KREATIF DI DESA AIR KERUH - Reni Septiyanti; Athirah Rifa Aulya; Iyamsi; Aisyah Hapsari; Chelsea Olivia; Nabila Regina Putri; Muhammad Ferdy Hasan; Heliza Dwi Wulandari; Elisia Modesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2026)
Air Keruh Village, Rambang District, Muara Enim Regency, South Sumatra, has significant human resource potential that has not been optimally utilized, particularly among women, whose labor force participation rate remains relatively low at approximately 28%. The majority of residents work as rubber and oil palm farmers with fluctuating incomes. This condition highlights the need for alternative income sources based on the creative economy. This community service program aimed to enhance skills and foster entrepreneurial spirit among housewives and young women through training in producing resin-based keychains. The implementation method consisted of socialization, training through lectures, demonstrations, and hands-on practice, as well as process and outcome evaluations, involving 25 participants. The results indicated that 88% of participants were able to produce resin keychains that met quality standards and had market value. In addition to improving technical skills, the activity increased entrepreneurial motivation and created opportunities for developing community-based microenterprises that can be marketed locally and through digital platforms as a sustainable strategy for strengthening the village economy.